Leveraging Artificial Intelligence in Web Development to Optimize Marketing Strategies for Vocational Student Products - Frinto Tambunan; Junerdi Nababan; Mutiha Aristo Ravel; Tri Budiarti Damanik; Alwin Fau (Penerbit Goodwood, 2026)
Purpose: This community service initiative aimed to assist students at Sekolah Menengah Kejuruan (SMK) Sultan Iskandar Muda in enhancing their digital competencies, specifically by developing professional Artificial Intelligence (AI) driven marketing websites to showcase their creative outputs. This research addressed the technical programming barriers that frequently hinder vocational students from marketing their work professionally through digital platforms. Methodology: Employing a quasi-experimental approach with a pretest-posttest design, this study involved 70 students from grades XI and XII. The intervention consisted of intensive training and hands-on practice in constructing marketing sites using Artificial Intelligence tools. Results: The findings revealed a statistically significant improvement in student comprehension, as evidenced by an increase in the mean scores from 53.5 to 82.8. Furthermore, all participants successfully deployed aesthetic and functional marketing websites. Conclusions: This study demonstrates that AI integration effectively mitigates coding complexities for vocational students, allowing them to prioritize digital business strategies and creative development. Limitations: The constraints identified included limited on-site mentoring duration and suboptimal Internet stability, which impacted cloud-based data synchronization during practical sessions. Contributions: This study provides a strategic reference for vocational institutions to design modern and innovative entrepreneurship curricula aligned with the demands of the digital transformation era.